Malignant bowel obstruction: a comparison among pre-operative factors, surgical approaches, and survival. Is surgery worthwhile? - G. Caldas, Tarsila; A. Pinto, Rodrigo; R. Nahas, Caio S.; E. Corbi, Leonardo; R. Júnior , Ulysses; F. S. Marques, Carlos (International Surgery Journal, 2023)
Background: Malignant bowel obstruction (MBO) is defined as the evidence of obstruction distally to the Treitz ligament in the presence of a malignant peritoneally disseminated neoplasm. Patients with this condition suffer from decreased quality of life due to impaired food intake, recurrent nausea, and abdominal pain. The objective was to investigate the outcome of patients with MBO surgically treated, considering post-treatment survival, surgical morbidity, and length of hospital stay, in order to assess the efficiency and impact of surgery at this advanced stage of disease. Methods: We reviewed retrospectively data collected from 198 patients diagnosed with MBO at Instituto do Câncer do Estado de São Paulo (ICESP), operated between 2018 and 2021. Results: Among preoperative factors, advanced stages and poor clinical status were associated with earlier death (stage IV had 4.53 higher chance of death). On the other hand, patients considered candidates for invasive life support measures had longer postoperative survival (non-candidates had a chance 1,000,000 times higher of death). Primary diagnosis also showed to be an important risk factor: ovary malignancies had higher risk of surgical complications (OR of 14.28), when compared to gastric and colon cancers. Considering intraoperative factors, patients who underwent resections had better long-term survival (9.9 months) than those who underwent bypass (1.3 months) or stomas (2 months); p=0.017. Finally, considering post-operative factors, long-term survival was associated with shorter hospital stay (p=0.001). Conclusions: Medical and surgical treatment should be employed on a case-by-case basis, after taking into consideration multiple pre-operative factors, such as KPS and primary tumor stage.